ANALYSIS OF LEARNING PREFERENCES AND STYLES OF STUDENTS IN AGRIBUSINESS PLANT EDUCATION - Suratman, Ikhsan Hidayat; Nurwahyunani, Atip; Cahyati, Zubaidah Gesit (BIOMA : Jurnal Ilmiah Biologi, 2025)
Agribusiness vocational education has a strategic role in preparing skilled workers who are able to compete in the world of work. This study aims to analyze the preferences and learning styles of students in the Food Crops and Horticulture Agribusiness program at SMK Negeri 1 Bawen. The research method used is quantitative descriptive with data collection through questionnaires and interviews. The main focus of this study includes preferences for learning methods, learning methods, enthusiasm levels, and other supporting factors such as access to agricultural land and learning facilities. The results showed that 48.28% of students preferred a combination of theory and practice learning methods because they provided a deeper understanding and were relevant to the needs of the world of work. As many as 79.31% of students chose to study in groups because they allowed discussion and collaboration, while 20.69% of students preferred independent learning to focus on individual understanding. The level of student enthusiasm for agribusiness learning varied, with the majority showing high involvement especially in field practice activities. Supporting factors such as access to agricultural land, practice facilities, and teacher support played a significant role in increasing student motivation and skills. This study concludes that a balanced learning approach between theory and practice, supported by adequate facilities and cooperation with the industrial world, can optimize student learning outcomes. Recommendations include the development of an industry-based curriculum and increased support for students who do not have access to agribusiness land.